If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y = -8y Solving y = -8y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '8y' to each side of the equation. y + 8y = -8y + 8y Combine like terms: y + 8y = 9y 9y = -8y + 8y Combine like terms: -8y + 8y = 0 9y = 0 Divide each side by '9'. y = 0 Simplifying y = 0
| 17/5=x/13 | | 5(y-2)=4y-1 | | y=-3x+13 | | -3x+12=7 | | 4x^2-84=-5x | | 7(5x+3)=(2x+19) | | a+2ax= | | 4y^2-4y+6x-15=0 | | 3.7x-46=1.2x+9 | | -3.5x+2.2=-25.8 | | 2x^2-5x+a=0 | | 7(5x+4)=(2x+19) | | 7(3x/1)=-1 | | 4n^2+16n+12=0 | | 5x-7=0.5(10+2x) | | 5+-5=5+-7 | | X^3+12x^2+36=0 | | 2x-4x+2=6 | | -80/3=d | | -24x+25x^2=0 | | 3x-5.2=-0.2(x-6) | | 6x^2-102x+432=0 | | -(3x-5)-(2x-6)+1=-5(x-1)-3(x+2)+3 | | -8k/-7=8 | | Y+5=-18 | | 2b-52=22 | | 6(4x+2)=2(34+2) | | (2x+5)-(x+2)= | | 3y-1=5y-9 | | 0.5x-20=-10 | | 3a+6a=45 | | 2.5x+5=7.5 |